Sensitivity of the ITCZ Location to Ocean Forcing Via Q‐Flux Green's Function Experiments - Bryce E. Harrop; Jian Lu; Fukai Liu; Oluwayemi A. Garuba; L. Ruby Leung (Geophysical Research Letters)
Abstract The sensitivity of the intertropical convergence zone (ITCZ) position to forcing patterns is important for understanding changes in tropical rainfall. A set of Green's function experiments reveals hat this sensitivity is asymmetric depending on which hemisphere (northern or southern) the forcing is applied. Northern hemisphere forcings produce a much larger response than southern hemisphere forcings of similar magnitude. The response of the ITCZ position to forcing can be broken into linear and nonlinear components, and it is shown that the asymmetry arises from the nonlinear component. The linear and nonlinear response components have similar magnitudes, but the pattern of the nonlinear component is insensitive to the location of the forcing, such that it amplifies the response to northern hemisphere forcings and dampens the response to southern hemisphere forcings. This asymmetry hints at an intrinsic mode of the climate system, depending on the current climate state.